Clinical and demographic characteristics of patients with nosocomial pneumonia against a background of severe traumatic brain injury - A.B. Ilchenko (Zaporožskij Medicinskij Žurnal, 2017)
Introduction. Nosocomial pneumonia (NP) is one of the most dangerous infectious complications of severe traumatic brain injury (TBI). According to some researchers, NP formed 0.5–1 % of hospitalized patients and in patients of ICU – NP develops with a frequency from 15 to 65 %.